Tungsten and molybdenum co-precipitation by α-benzoinoxime for activation analysis of tungsten - Korob, Ricardo Osvaldo; Cohen, Isaac Marcos; Agatiello, Omar Emilio (Elsevier Sequoia, 1976)
Fil: Korob, Ricardo Osvaldo Comisión Nacional de Energía Atómica; Argentina